Do employment subsidies reduce early apprenticeship dropout? - Fries, Jan [Verfasser]; Goebel, Christian [Verfasser]; Maier, Michael F. [Verfasser] (My University, 2014)
"We evaluate the effect of the Apprenticeship Bonus, an employment subsidy program, on early drop out of apprenticeship. Only school leavers who did not succeed to start apprenticeship training directly after leaving school are eligible for this program. Our analysis is based on rich survey data that has been collected specifically for this study. Using this data, we investigate the selection into the program and analyze the effect of this subsidy on apprenticeship drop out risk. Even though the subsidy provides strong incentives to prevent drop out, we do not find significant effects of the program on early drop out of subsidized apprentices. Our finding suggests that financial incentives are not efficient in increasing the probability to finish vocational in-firm training successfully." (Autorenreferat; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); Ausbildungsplatzförderung; Ausbildungsbonus; Erfolgskontrolle; Altbewerber; Ausbildungsabbruch; Einflussfaktor